2012
DOI: 10.1007/s00464-012-2153-3
|View full text |Cite
|
Sign up to set email alerts
|

Nerve-sparing laparoscopic eradication of deep endometriosis with segmental rectal and parametrial resection: the Negrar method. A single-center, prospective, clinical trial

Abstract: Our technique appears to be feasible and offers good results in terms of reduced bladder morbidity and apparently higher satisfaction than the classical technique. Considering that this kind of surgery requires uncommon surgical skills and anatomical knowledge, we believe that it should be performed only in selected reference centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
140
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(151 citation statements)
references
References 64 publications
5
140
2
4
Order By: Relevance
“…Authors showed that urinary retention was more frequent and ISC was longer in the group without this procedure. The authors say this technique could be quicker, without more immediate per-and post-operative complications and would also decrease the rate of severe pelvic neurological dysfunctions (urinary, digestive and genito-sexual) [24].…”
Section: Discussionmentioning
confidence: 99%
“…Authors showed that urinary retention was more frequent and ISC was longer in the group without this procedure. The authors say this technique could be quicker, without more immediate per-and post-operative complications and would also decrease the rate of severe pelvic neurological dysfunctions (urinary, digestive and genito-sexual) [24].…”
Section: Discussionmentioning
confidence: 99%
“…27 Darai et al 15 reported a 12.6% major complication rate following laparoscopic segmental bowel resection. 39 Long-term bladder and bowel dysfunction (urinary retention, tenesmus, frequency of defecation) are often the most disabling long-term complications encountered by patients following radical surgery. Rectal shaving certainly avoids the need for deep lateral rectal dissection and hence preserves the pelvic autonomic nerves and thus as expected fewer bladder and bowel complications are reported post-operatively, 35 however once again this must be balanced again the risk of residual disease and recurrence.…”
Section: Bowel Endometriosismentioning
confidence: 99%
“…Gastrointestinalis lae siók az esetek 5,3-12%-ában jelennek meg [1,4,5,6,7]. A DIE érintheti a kismedence elülső régióját is, jelentkezhet a plica vesicouterinán és infi ltrálhatja a húgyhólyag izomzatát.…”
Section: Eredeti Közleményunclassified